Neurodevelopment in normocephalic children exposed to Zika virus in utero with no observable defects at birth: a systematic review with meta-analysis - Marbán-Castro, Elena; Vazquez Guillamet, Laia J.; Pantoja, Percy Efrain; Casellas, Aina; Maxwell, Lauren; Mulkey, Sarah B.; Menéndez, Clara; Bardají, Azucena (International journal of environmental research and public health, 2022)
Zika virus (ZIKV) infection during pregnancy is a cause of pregnancy loss and multiple clinical and neurological anomalies in children. This systematic review aimed to assess the effect of ZIKV exposure in utero on the long-term neurodevelopment of normocephalic children born to women with ZIKV infection in pregnancy. This review was conducted according to the PRISMA guidelines for systematic reviews and meta-analyses. We performed a random effects meta-analysis to estimate the cross-study prevalence of neurodevelopmental delays in children using the Bayley Scales for Infant and Toddler Development (BSID-III). The risk of bias was assessed using Cochrane’s Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach. Full-text reviews were performed for 566 articles, and data were extracted from 22 articles corresponding to 20 studies. Nine articles including data from 476 children found 6.5% (95% CI: 4.1-9.3) of infants and children to have any type of non-language cognitive delay; 29.7% (95% CI: 21.7-38.2) to have language delay; and 11.5% (95% CI: 4.8-20.1) to have any type of motor delay. The pooled estimates had a high level of heterogeneity; thus, results should be interpreted with caution. Larger prospective studies that include a non-exposed control group are needed to confirm whether ZIKV exposure in utero is associated with adverse child neurodevelopmental outcomes.
Gesehen am 25.08.2022
This article belongs to the special issue "Frontiers in maternal and reproductive health"